UKIP's Performance in the 2015 General Election: A Series of Unfulfilled Expectations - Karine Tournier-Sol (Revue Française de Civilisation Britannique)
As 2015 began, UKIP's electoral prospects for the upcoming general election looked definitely good; expectations were high among the Ukippers, all the more so since another hung parliament seemed very likely, possibly giving the party a role to play in determining the balance of power. As it turned out, the results fell short of the party's expectations as UKIP only returned one MP to Westminster. This paper aims at assessing UKIP's performance in the 2015 general election by first focusing on the campaign, in which the party found it hard to capture attention, despite Nigel Farage's confrontational tactics. The election was also marked by the party's efforts to demonstrate that it had reached a new stage in its evolution and had gained credibility, notably through a wide-ranging and fully-costed manifesto, which will be examined in a second part. Finally, although the "UKIP effect" was not as significant as expected, the results of the election will be analysed and put into perspective in the third part, also reflecting on the brief civil war which erupted in the party ranks in the aftermath of the election. The paper will conclude on the party's prospects in the perspective of the EU referendum which David Cameron's victory has now firmly set on the political agenda.